Learned Physicians and Everyday Medical Practice in the Renaissance - Stolberg, Michael (2021)
Michael Stolberg offers the first comprehensive presentation of medical training and day-to-day medical practice during the Renaissance. Drawing on previously unknown manuscript sources, he describes the prevailing notions of illness in the era, diagnostic and therapeutic procedures, the doctor-patient relationship, and home and lay medicine.